Impact of cytidine diphosphocholine on oxygenation in client‐owned dogs with aspiration pneumonia. (29th April 2022) - Young, Anda A.; Rosas, Lucia E.; Cooper, Edward S.; Yaxley, Page E.; Davis, Ian C.
Abstract: Background: New drugs for veterinary patients with acute respiratory distress syndrome (ARDS) are urgently needed. Early or late postinfection treatment of influenza‐infected mice with the liponucleotide cytidine diphosphocholine (CDP‐choline) resulted in decreased hypoxemia, pulmonary edema, lung dysfunction, and inflammation without altering viral replication. These findings suggested CDP‐choline could have benefit as adjunctive treatment for ARDS in veterinary patients (VetARDS). Objectives: Determine if parenterally administered CDP‐choline can attenuate mild VetARDS in dogs with aspiration pneumonia. Animals: Dogs admitted to a veterinary intensive care unit (ICU) for aspiration pneumonia. Methods: Subjects were enrolled in a randomized, double‐blinded, placebo‐controlled trial of treatment with vehicle (0.1 mL/kg sterile 0.9% saline, IV; n = 8) or CDP‐choline (5 mg/kg in 0.1 mL/kg 0.9% saline, IV; n = 9) q12h over the first 48 hours after ICU admission. Results: No significant differences in signalment or clinical findings were found between placebo‐ and CDP‐choline‐treated dogs on admission. All dogs exhibited tachycardia, tachypnea, hypertension, hypoxemia, hypocapnia, lymphopenia, and neutrophilia. CDP‐choline administration resulted in rapid, progressive, and clinically relevant increases in oxygenation as determined by pulse oximetry and ratios of arterial oxygen partial pressure (Pa O2 mmHg) to fractional inspired oxygen (% Fi O2 ) and decreases in alveolar‐arterial (A‐a) gradients that did not occur in placebo (saline)‐treated animals. Treatment with CDP‐choline was also associated with less platelet consumption over the first 48 hours, but had no detectable detrimental effects. Conclusions and Clinical Importance: Ctyidine diphosphcholine acts rapidly to promote gas exchange in dogs with naturally occurring aspiration pneumonia and is a potential adjunctive treatment in VetARDS patients.